PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DAN SELF EFFICACY TERHADAP HIGHER ORDER THINKING SKILL (HOTS) MATEMATIKA PESERTA DIDIK - Lesa Taman Sari (EDU RESEARCH, 2024)
This study aims to determine the effect of the application of the Problem Based Learning (PBL) and Self-Efficacy Model of Students Against Students' Higher Order Thinking Skills (HOTS) Mathematics. This study uses a quasi-experimental design with a non-quivalent pre-test and post-test control group design. Based on the results of the study it can be concluded that there is an effect of the application of the Problem Based Learning (PBL) learning model to the Higher Order Thinking Skill (HOTS) of Student Mathematics. which is indicated by obtaining the value of F_count for model variables is 9,382, the value of F_count is compared with F_tabel which is 3.10 then it can be concluded that F_count> F_ (table) or 9.3382 > 3.10. there is no effect of students 'self-efficacy on students' higher order thinking skills (HOTS) mathematics. seen that the value of F_calculated for the Self Efficacy questionnaire was 0.285 while the value of F_table was 3.10, when compared to F_count 〖<F 〗table or 0.285 < 3.10. there is no interaction between the application of the Problem Based Learning (PBL) learning model and students 'self-efficacy towards students' higher order thinking skills (HOTS) mathematics. it can be seen that the calculated F_ value for the factors for the learning model and Self-Efficacy variables is 0.697 while the F_ value (table) is 3.10. When compared, it can be concluded that F_count < F_tabel or 0.697 < 3.10.